The Cancer Genome Atlas (TCGA) based m6A methylation-related genes predict prognosis in hepatocellular carcinoma. Issue 1 (1st January 2020) - Liu, Jun; Sun, Guili; Pan, Shangling; Qin, Mengbin; Ouyang, Rong; Li, Zhongzhuan; Huang, Jiean
ABSTRACT: The current study aims to investigate the significance of N 6 -methyladenosine (m 6 A) methylation-related genes in the clinical prognosis of hepatocellular carcinoma (HCC) using bioinformatics analyses based on The Cancer Genome Atlas (TCGA) database. Transcriptome data and corresponding clinical data on m 6 A methylation-related genes (including 15 genes) were obtained from TCGA database. Differential expression of 15 genes was identified. Survival curves of subgroups based on m 6 A methylation-related gene expression levels were plotted. We selected potential predictive genes and analyzed their prognostic values using bioinformatics methods. Eleven genes ( METTL3, YTHDF1, YTHDF2, YTHDF3, YTHDC1, YTHDC2, FTO, KIAA1429, HNRNPC, HNRNPA2B1, and RBM15 ) were found to be overexpressed in HCC. Of these, five genes had worse survival (P < 0.05). There was a significant difference in the survival rate between subgroups with different expression levels of m 6 A. We selected five potential predictors ( METTL3, KIAA1429, ZC3H13, YTHDF1, and YTHDF2 ) that met the independent predictive value. ZC3H13 was upregulated in patients with high cancer risk, whereas METTL3, KIAA1429, YTHDF1, and YTHDF2 were downregulated. In summary, we found that the expression levels of m 6 A methylation-related genes were different in patients with HCC and correlated with survival and prognosis. This implies that m 6 A methylation-related genes may be promising prognostic indicators or therapeutic targets for HCC. Graphical abstract: